(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Ayurvedic philosophies are the concepts of "Swasthavritta," which encompass key determinants of health- diet, lifestyle, sleep, and mental well-being that maintain balance and prevent disease. In Ayurveda, health is defined as the harmonious integration of these factors, rather than simply the absence of illness. This review explores the foundational principles of Ayurvedic health determinants, examining their theoretical basis, clinical applications, and their potential contribution to modern healthcare systems. By addressing factors such as individual constitution (Prakriti), digestion (Agni), and emotional well-being, Ayurveda provides a personalized framework for preventing and managing chronic diseases. Incorporating Ayurvedic practices, including diet regulation, lifestyle modifications, and stress management, into contemporary medical paradigms could offer a more integrative and preventative approach to health. This paper highlights the potential of Ayurveda to complement modern healthcare practices by promoting patient-centered, holistic care that focuses on long-term wellness and disease prevention.